2019
DOI: 10.1111/mec.15061
|View full text |Cite
|
Sign up to set email alerts
|

Disease management at the wildlife‐livestock interface: Using whole‐genome sequencing to study the role of elk in Mycobacterium bovis transmission in Michigan, USA

Abstract: The role of wildlife in the persistence and spread of livestock diseases is difficult to quantify and control. These difficulties are exacerbated when several wildlife species are potentially involved. Bovine tuberculosis (bTB), caused by Mycobacterium bovis, has experienced an ecological shift in Michigan, with spillover from cattle leading to an endemically infected white-tailed deer (deer) population. It has potentially substantial implications for the health and well-being of both wildlife and livestock an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
55
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 76 publications
8
55
1
2
Order By: Relevance
“…The distribution for the substitution rate ( μ ) was a beta-PERT, with mode, minimum and maximum respectively set to 0.31, 0.1 and 0.94 base pair × genome × year. These values corresponded to the average, minimum, and maximum of literature estimates from other systems 27,59–61 . We assigned a similar prior to the latency period ( 1/σ ), based on the published literature for data relevant to the geographical area (south-east England).…”
Section: Methodssupporting
confidence: 76%
“…The distribution for the substitution rate ( μ ) was a beta-PERT, with mode, minimum and maximum respectively set to 0.31, 0.1 and 0.94 base pair × genome × year. These values corresponded to the average, minimum, and maximum of literature estimates from other systems 27,59–61 . We assigned a similar prior to the latency period ( 1/σ ), based on the published literature for data relevant to the geographical area (south-east England).…”
Section: Methodssupporting
confidence: 76%
“…Whole-genome sequencing of M. bovis has been used to track transmission within and between cattle and wildlife populations [21,[33][34][35][36][37]. These studies have demonstrated that genomics adds unprecedented resolution, in comparison to previous molecular-typing technologies, in many cases distinguishing infection between individual animals.…”
Section: Introductionmentioning
confidence: 99%
“…Many aspects of animal TB epidemiology are yet to be elucidated, which limits the estimation of transmission model parameters. Disease modelling approaches could be helpful in decision‐making, by evaluating potential alternative diagnostic and control measures in high prevalence scenarios (Guta et al, 2014); and to improve surveillance and streamline the eradication strategies in low prevalence scenarios, when a disease outbreak occurs (Salvador et al, 2019), never losing the heterogeneity parameter from the equation. The way these knowledge gaps are considered within the mathematical models, and the different considered assumptions, may have a critical impact on the model outcomes and robustness, so extrapolation of results to a certain scenario and the underlying definition for interventions should be done with caution (Álvarez et al, 2014; Conlan et al, 2012).…”
Section: Implications Of Animal Tb Heterogeneity In Management Contrmentioning
confidence: 99%